Research on the current state of english electronic education terminological fund (Eurasian Journal of Philology Science and Education, 2019)
This article is devoted to the study of electronic education terminological fund in the modern English language and its current state. The distribution of new English terms in the communication space ofKazakhstan and their intensive use is due to the processes of modernization and digitalization of education. In this work we consider 294 terms, analyzing their specific characteristics, classifying componentsaccording to the principle of productivity. The analysis of the studied terms made it possible to identifythe dominant term in the group of synonyms denoting electronic education - e-learning. This article alsodiscusses groups of terms that need to be clarified due to definitive variability and the lack of a generallyaccepted point of view on their meaning. The research shows that processes occurring in the sphere ofelectronic educational environment are directly reflected in the expansion of the terminology of electronic education. The current state of the terminology fund of electronic education is characterized bydynamism and the presence of a large number of terms that reflect related concepts. This article proposesthat uncovered specifics and features for the groups of terms researched in this article are generally validfor electronic education terminological fund in the modern English language. The article predicts thatfurther research and linguistic analyses of term groupings in the sphere of electronic education givesopportunity to elicit trends and developing tendencies of English terminological fund as a whole. Asystematic study of e-learning terminology will reveal intrasystem correlations of terminological units.The abovementioned analyses results allow researchers to model possible directions and patterns ofelectronic education terminological fund development in the modern English language.